Drinking alcohol raises the chance of premarital sex by four folds among secondary school adolescent students in Jima Arjo, Southwestern Ethiopia, 2018: a school-based cross-sectional study - Bayisa Biratu; Sileshi Garoma; Motuma Getachew; Markos Desalegn (BMC, 2022)
Abstract Background Premarital sexual practice is sexual intercourse performed before formal marriage. Pre-marital sexual practice increases adolescents' risk for having multiple sexual partners, (sexually transmitted disease) STDs, and unintended pregnancy. Objective The study aimed to assess the prevalence of premarital sexual practice and associated factors among secondary school (9-12 grade) students in the Jima Arjo district. Methods Institutional-based cross-sectional study design was conducted among adolescent students from May 1st to 15th using a pre-tested and structured questionnaire. A systematic random sampling technique was employed to select study participants. The collected data was cleaned and entered into(statistical package for social science) SPSS version 20. Factors associated with the pre-marital sexual practice were identified by multiple logistic regression analyses. Results The over all premarital sexual practice in this study area was 24.4%. Being alcoholdrinker(AOR[95%CI] = 3.78[1.49,22.08]),havingaboy/girlfriend(AOR[95%CI] = 5.07[3.74,26.47]), (being male) (AOR[95%CI] = 2.9[1.78,37.8]); urban residence (AOR[95%CI] = 6.44 [1.95,25.84]). Conclusions The study revealed that a significant proportion of adolescent students in this study area practiced premarital sex. Being male sex, urban residence, using alcohol use and having a boy/girlfriend significantly affect premarital sexual practice. Therefore, school and community-based sexual health education, and communication need to be intensified to reduce premarital sex and further health consequences.